2009
DOI: 10.1007/s11665-009-9538-z
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Particle Emission During Dry Orthogonal Cutting

Abstract: Because of the risks associated with exposure to metallic particles, efforts are being put into controlling and reducing them during the metal working process. Recent studies by the authors involved in this project have presented the effects of cutting speeds, workpiece material, and tool geometry on particle emission during dry machining; the authors have also proposed a new parameter, named the dust unit (D u ), for use in evaluating the quantity of particle emissions relative to the quantity of chips produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Likewise, demolition of high rise buildings in Chicago (Illinois, USA) showed between 4 and 9 times increase of 6-h averaged PM 10 concentrations against the background at 42 m downwind of demolition site (Dorevitch et al, 2006). While numerous studies are available on the dust emissions from activities such as arc welding (Lee et al, 2007), drilling (Shan et al, 2012), cutting (Khettabi et al, 2010), unintentional release of airborne nanoparticles from major building activities such as construction, demolition, recycling and refurbishment is largely unknown. As discussed in subsequent sections, only a handful of studies have looked into this topic but none of them offer much information on the number and size distributions released from different building activities, their emission strength or physicochemical characteristics, or possible exposure and health impacts.…”
Section: Source Characteristics and Nanoparticle Formationmentioning
confidence: 99%
“…Likewise, demolition of high rise buildings in Chicago (Illinois, USA) showed between 4 and 9 times increase of 6-h averaged PM 10 concentrations against the background at 42 m downwind of demolition site (Dorevitch et al, 2006). While numerous studies are available on the dust emissions from activities such as arc welding (Lee et al, 2007), drilling (Shan et al, 2012), cutting (Khettabi et al, 2010), unintentional release of airborne nanoparticles from major building activities such as construction, demolition, recycling and refurbishment is largely unknown. As discussed in subsequent sections, only a handful of studies have looked into this topic but none of them offer much information on the number and size distributions released from different building activities, their emission strength or physicochemical characteristics, or possible exposure and health impacts.…”
Section: Source Characteristics and Nanoparticle Formationmentioning
confidence: 99%
“…Khettabi et al (2010a) developed a hybrid model of particle emission during machining processes which was based on the energy approach, combined with macroscopic friction (tool-chip), microfriction, and plastic deformation of materials:…”
Section: Understanding and Modeling Particle Emissionsmentioning
confidence: 99%
“…The rotation of the drill during machining creates an airflow movement around the drill tool, which results in the dispersion of dust generated at the cutting zone. The size and quantity of the dust depend on the cutting parameters, the workpiece, and the tool material [26,31]. The aerodynamic particle sizer (APS) measures particles from 0.5 to 10 µm, and presents these results by parameters such as number concentration, mass concentration, and specific surface concentration, as a function of aerodynamic diameters.…”
Section: Fine Particle Emissionmentioning
confidence: 99%
“…The dust generated during machining of metallic materials has been studied by several researchers [21][22][23][24][25][26][27][28][29][30][31], who observed that the relationship of the dust emission with cutting conditions such as the workpiece material, tools, and cutting parameters [21,28,31]. Small size dust emitted during machining has a significant impact on the environment and on the health of machine operators [22,29].…”
Section: Introductionmentioning
confidence: 99%